Social determinants and chronic kidney disease of undetermined origin in childhood: Its communication and understanding described by families in Lake Chapala, Mexico - Ruiz-Velazco, Norma Guadalupe; Lozano-Kasten, Felipe de Jesús; Guzman-Torres, Horacio; Mejía-Sanchez, Aaron Ismael (Frontiers in Nephrology, 2022)
This work is based on the recognition of the existence of a complex relationship between social and environmental determinants and infants with chronic kidney disease of epidemic type of undetermined origin. The aim is to understand how the Social and Environmental Determinants are configured and reconfigured, and the chronic kidney disease of undetermined origin in childhood, through knowledge built from the population that has lived the experience of the disease. This research was carried out with a narrative-conversational design. The experience of CKD was organized in stories focused on the experience of families in the social and environmental context where they live, get sick, suffer, and die from the disease. In the dialogue emerges the intersection of the social determinants of the disease, the different ways of life, and the relationship with the health services that attend them.